Math Teachers' Professionalism After Motivation Training: A Contextual Approach - Marhan Taufik; Reni Dwi Susanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Professional educators can carry out their primary duties as educators and teachers, including planning lessons, implementing, and evaluating learning outcomes according to their fields. The problem of competence is one of the factors in the development of the educator as a professional position. It is necessary to research the formulation of how professional mathematics educators are after giving motivation training using a contextual approach. The type of research used is descriptive with a qualitative approach. Observation and questionnaires are data collection techniques used to collect data. Observations were made to obtain information about how the implementation of learning was carried out by educators after the motivation training. At the same time, the questionnaire was used to collect data related to the effect of giving motivation training. Analysis of the data used in this study is to examine the results of observations and the questionnaire results. Then the results are described with support and strengthened by the findings during the implementation of activities. The results showed that the analysis of the provision of motivation with a contextual approach carried out had a good impact on the quality of learning.